Promoting the Financing of SMEs and Start-ups in Korea - Jones, Randall S.. (OECD Publishing, 2014)
The Korean government has made fostering a "creative economy" a top priority. The goal is to shift Korea's economic paradigm to one based on innovation in which new start-ups and venture businesses play a key role. However, the venture capital market is still at an early stage of development. To make venture investment a growth driver, it is important to expand the role of business angels, activate the merger-andacquisition market and foster entrepreneurship. A creative economy also depends on making SMEs, which account for 87% of employment, more dynamic. The productivity gap between large firms and SMEs, which benefit from a wide range of public support, is widening. SME policies should be streamlined and improved to promote market-based financing and reduce the negative effects of government funding programmes, which discourage the expansion of SMEs
Keywords: Economics; Industry and Services; Korea, Republic of